A systematic review protocol of medical and clinical research landscapes and quality in Malaysia and Indonesia (REALQUAMI) - Chew, Boon-How; Huey Lee, Shaun Wen; Ying, Lim Poh; Teoh, Soo Huat; Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Ismail, Adibah Hanim; Abdul Manap, Abdul Hadi; Mohamad, Fadzilah; Fernandez, Aaron; Ali, Hanifatiyah; Jahn Kassim, Puteri Shanaz; et al. (AccScience Publishing, 2025)
Background: The evolving landscape of clinical and biomedical research has raised concerns about waste and quality. Poorly conducted studies mislead clinical practice and compromise patient outcomes. Reliable data from past research are essential for research quality improvement. Aim: The aim of the study was to characterize and assess the quality of research in Malaysia and Indonesia. Methods: To establish the proposed systematic review protocol, we will search PubMed, Cochrane Library, CINAHL, and PsycINFO for studies published from 1962 to 2019, supplemented by MyMedR for Malaysian research. Two reviewers will independently screen studies, extract data, and assess quality. Phase 1 will descriptively report research characteristics, including researcher profiles and journal outlets. In Phase 2, a quality screening tool will be validated across three domains: relevance, methodological credibility, and result usefulness. Associations between research characteristics and quality will be analyzed through multivariable regression and longitudinal trends will be explored. Results: Findings from the proposed systematic review protocol will generate baseline data for national and international comparisons, guiding stakeholders, researchers, funders, and policymakers on research evolution and quality trends. Results may inform improvement initiatives and resource allocation for understudied areas. Conclusion: This review aims to establish a comprehensive baseline of research outputs and the pattern of research quality in the participating countries and discipline. The findings may underscore the presence of a valid classification method to guide future research and enhance evidence-based practice in healthcare. Relevance for patients: By identifying research strengths and gaps, this proposed systematic review supports the development of robust study designs that generate reliable evidence, ultimately enhancing patient care and health outcomes.